Do I dare disturb the universe? : a memorial to W.R. Bion - Grotstein, James S. (Maresfield library., 2003)
All the contributors to this compilation knew Bion personally and were influenced by his work. They include: Herbert Rosenfeld, Frances Tustin, Andre Green, Donald Meltzer and Hanna Segal. 674 pages.